Mobile ad-hoc routing protocols survey for the design of VANET applications (2012)
Vehicular communications are considered as a key factor to improve road safety and enhance urban mobility. The design and deployment of Vehicular Ad hoc Networks (VANETs) involve several decision criterias that lead the research into new challenging tasks to be solved. Routing mechanism is a fundamental component for the success of any vehicular application; the particular features of VANETs - a highly dynamic topology, links frequently disrupted and a fragmented network - require an efficient, robust and scalable routing strategy for each application. In this paper, we present a survey of routing protocols and we also provide a simulation testbed that will be used to assess the performance of the selected protocols. © 2012 IEEE.